OPTIMIZING MULTIPLICATION LEARNING IN ELEMENTARY SCHOOLS THROUGH THE JARIMATIKA METHOD - Tri Kurniah Lestari; Sherina Soyan; Ratnawati Ratnawati; Karina Nurwijayanti; Sri Wahyuni (Jurnal PTK dan Pendidikan, 2025)
Abstract The aim of this study is to describe the multiplication skills of fourth-grade students at SDN Inpres Ardipura III Jayapura using the Jarimatika method and to examine the teacher's efforts to improve these skills. This is a qualitative study using Classroom Action Research (CAR) design, which was carried out in two cycles. The subjects of this study were all 30 students of the fourth grade at SDN Inpres Ardipura III Jayapura during the 2022/2023 academic year. Data collection methods included interviews, observation, tests, and documentation. Content validity was applied to ensure data validity, and interactive analysis techniques were used for data analysis. The results of this classroom action research, conducted in two cycles with the implementation of the Jarimatika method, showed a significant improvement in students' multiplication skills. The initial condition, before any intervention, showed an average score of 52.83 with a classical completeness percentage of 57%. In the first cycle, the average score increased to 63.50 with a classical completeness percentage of 63%. By the second cycle, the average score had risen to 76.17 with a classical completeness percentage of 87%. These findings indicate that, classically, the learning process achieved the minimum mastery criteria. Therefore, it can be concluded that the use of the Jarimatika method effectively enhances the multiplication skills of fourth-grade students at SDN Inpres Ardipura III Jayapura. Keywords: Jarimatika method, Multiplication operation, Classroom Action Research.Â